POTENSI BUDAYA SUKU TORAJA SEBAGAI DAYA TARIK WISATA PADA KABUPATEN TANA TORAJA DAN TORAJA UTARA - Winowatan, Wim Johannes; Anneke W, Jeanny Pricilia (Tulisan Ilmiah Pariwisata (TULIP), 2023)
This study aims to determine the cultural potential of the Toraja tribe as a tourist attraction in Tana Toraja and North Toraja districts. With the research method using the type of data used by the author is qualitative data, namely a study aimed at describing and analyzing phenomena, events, activities, social, attitudes, beliefs, perceptions, thoughts of people individually and in groups. In this study, the data obtained was based on the source, namely Primary Data. This data was obtained while the researcher was making observations in Tana Toraja and North Toraja Regencies. The data obtained in the form of images, facilities and files. Then Secondary Data Is data obtained from the source indirectly but has been collected by other parties and has been processed, in the form of archives, books, reports, and several documents. With data collection techniques, namely observation and literature study and documentation so that data analysis is carried out using descriptive qualitative. And the results of the research show that basically there are so many Toraja ethnic cultures which are very unique and still traditional which should be used as a tourist attraction and become a potential big event so as to advance Toraja society and at the same time introduce one of the thick cultures that is still very original and unique in the world of tourism. tribe living in the mountains of the northern part of South Sulawesi, Indonesia. Its population is estimated at around one million people, with 500,000 of them still living in Tana Toraja, North Toraja, and Mamasa districts. Thus, the Toraja tribe and culture have the potential to become a sustainable tourist attraction for the world.